Dr. Ernesto Galarza Scholarship Symposium Program 1998 - Chicano/Latino Faculty and Staff Association::::::::::::::: (2024)
Program for the Dr. Ernesto Galarza Scholarship Symposium, held at San Jose State University on Wednesday, September 16, 1998 at 5:30 PM – 8:30 PM. This event included a Dr. Ernesto Galarza Commemorative Walk Dedication on Paseo de San Antonio at 4:00 PM, Reception, Welcome, Keynote by José Villa (former SJSU Faculty colleague and friend of Dr. Galarza), Presentation of Scholarships, and Closing Remarks. Eight awards were presented: Pueblos de San José Kiwanis Club Scholarship (2 awards), José Antonio Burciaga Scholarship, Chicano/Latino Faculty and Staff Association Scholarship, Cesar Chavez Memorial Scholarship, Dr. Ernesto Galarza Endowment Scholarship, Nu Alpha Kappa Scholarship, and Marisol Perez Scholarship.